Effect of coconut oil emulsion on encapsulation of lactobacillus bulgaricus and survival in simulated gastrointest conditions - Othman, N. I.; Shahril, M.; Ramli, S.; Malek, R. A.; Mohd. Noor, N.; Sarmidi, Mohamad Roji; Abdul Aziz, Ramlan (2007)
A technique was developed to protect lactic acid bacteria against high temperature during spray drying by encapsulation of bacteria cells within film-forming protein-carbohydrate- coconut oil emulsion. For these studies, the viability of the Lactobacillus bulgaricus was the highest in the feed formulation GANAMDO1 (containing 50% gum Arabic, 40% maltodextrin, 10% sodium caseinate w/w in oil/wall ratio=1) with 12.3 x 10-1 % viability after spray drying, surviving up to 2 times better than control cells (containing 100% gum Arabic in oil) at outlet air temperature 80-85Â°C. Increasing the proportion of the wall material (oil/wall ratio = 0.5) do not improved the viability of Lactobacillus bulgaricus after spray drying. The viable counts of spray dried Lactobacillus bulgaricus entrapped in GANAMDO1 were more than 3 log cycles than those obtained with others feed formulation after sequential exposure to simulated gastric and intestinal juices.